Anti-osteoporosis mechanism of resistance exercise in ovariectomized rats based on transcriptome analysis: a pilot study - Wang, Qing; Weng, Heng; Xu, Yue; Ye, Hui; Liang, Yongqi; Wang, Lulu; Zhang, Yutong; Gao, Yujie; Wang, Jiayi; Xu, Yuchen; Sun, Zhiling; Xu, Guihua (Frontiers in Endocrinology, 2023)
Postmenopausal osteoporosis is the main cause of fractures in women. Resistance exercise has a positive effect on bone mineral density in postmenopausal osteoporosis patients, but its mechanism is unclear. The purpose of this study was to explore the mechanism of resistance exercise in improving ovariectomized osteoporotic rats based on the transcriptome sequencing technique. Eighteen female Sprague-Dawley rats were randomly divided into the sham-operated group, the non-exercise group, and the resistance exercise group. The rat model of postmenopausal osteoporosis was established by bilateral ovariectomy. Ten weeks after the operation, the resistance exercise group received 2 weeks of adaptive training, and 12 weeks of resistance exercise began in the 13th week. The rats were trained 5 days per week, in 4 sets of 3 repetitions per day. After the intervention, all rats were sacrificed, and the body weight, bone mineral density, trabecular bone microarchitecture, and bone biomechanics were examined. At the same time, RNA-seq and enrichment analysis of gene ontology and Kyoto Encyclopedia of Genes and Genomes were performed on the left tibias, followed by Elisa and RT-qPCR verification. It had been found that resistance exercise can effectively counteract the weight gain of ovariectomized osteoporotic rats, and has a good effect on bone mineral density and trabecular bone microarchitecture. Enrichment analysis showed that regulation of gene expression and osteoclast differentiation is the most closely related biological process and signaling pathway shared by RE/Ovx and NE/Ovx groups. Our results revealed that resistance exercise can play a role in inhibiting osteoclast activation and preventing the enhancement of osteoclast bone resorption function in ovariectomized osteoporotic rats by inhibiting Fos/Fosb-regulated TRAP activation and relieving Calcr inhibition, which has important application value in preventing bone loss caused by estrogen deficiency.